Etika Hukum dan Korupsi di Sektor Publik: Studi Kasus Penegakan Hukum Anti-Korupsi Pasca-Reformasi - Endah Astuti; Wahyu Donri Tinambunan; Martha Parulina Berliana; Tri Setiadi (Jurnal Civic Hukum, 2026)
This article discusses the relationship between legal ethics and corruption in Indonesia’s public sector after the Reformasi era by using a normative-empirical approach and selected case studies. It explains the position of legal ethics in public governance, maps the transformation of corruption patterns after decentralization, and assesses the effectiveness of anti-corruption law enforcement through the e-KTP, BLBI, and Hambalang cases. The analysis shows that law enforcement has generated important achievements, particularly in exposing grand corruption, but its impact remains constrained by political intervention, uneven institutional capacity, weak asset recovery, and the fragile internalization of ethical standards within public institutions. The article argues that anti-corruption policy will be more effective when punitive mechanisms are integrated with ethical governance, bureaucratic reform, transparency systems, and public participation.